The Rising Incidence of Gout and the Increasing Burden of Comorbidities: A Population-based Study over 20 Years - Elfishawi, Mohanad M; Zleik, Nour; Kvrgic, Zoran; Michet, Jr, Clement J; Crowson, Cynthia S; Matteson, Eric L; Bongartz, Tim (Journal of rheumatology, 2018)
To examine the incidence of gout over the last 20 years and to evaluate possible changes in associated comorbid conditions. The medical records were reviewed of all adults with a diagnosis of incident gout in Olmsted County, Minnesota, USA, during 2 time periods (January 1, 1989-December 31, 1992, and January 1, 2009-December 31, 2010). Incident cases had to fulfill at least 1 of 3 criteria: the American Rheumatism Association 1977 preliminary criteria for gout, the Rome criteria, or the New York criteria. A total of 158 patients with new-onset gout were identified during 1989-1992 and 271 patients during 2009-2010, yielding age- and sex-adjusted incidence rates of 66.6/100,000 (95% CI 55.9-77.4) in 1989-1992 and 136.7/100,000 (95% CI 120.4-153.1) in 2009-2010. The incidence rate ratio was 2.62 (95% CI 1.80-3.83). At the time of their first gout flare, patients diagnosed with gout in 2009-2010 had higher prevalence of comorbid conditions compared with 1989-1992, including hypertension (69% vs 54%), diabetes mellitus (25% vs 6%), renal disease (28% vs 11%), hyperlipidemia (61% vs 21%), and morbid obesity (body mass index ≥ 35 kg/m ; 29% vs 10%). The incidence of gout has more than doubled over the recent 20 years. This increase together with the more frequent occurrence of comorbid conditions and cardiovascular risk factors represents a significant public health challenge.